Food Security on The Incidence of Stunting in Agricultural Areas - Najwa Zahira Shofa; Nisak Berliana Ahmad; Dzakia Raisa; Enggal Hadi Kurniyawan; Alfid Tri Afandi; Dicky Endrian Kurniawan; Kholid Rosyidi Muhammad Nur (KHD-Production, 2024)
Child stunting is a global health problem, and the national prevalence of stunting is high. Stunting indicates failure of child development due to chronic malnutrition. Other causes of stunting can also be influenced by food security, parenting, environmental sanitation, or access to health services. In agricultural areas, one of the efforts that the community can make to reduce stunting rates is to maintain food security to prevent stunting in children. This study aims to determine that food security can reduce the prevalence of stunting in agricultural areas. The literature search used Google Scholar, PubMed, and ScienceDirect databases. The inclusion and exclusion criteria of the articles included national and international articles using Indonesian and English from 2020-2024. It was found that local food security is effective in preventing stunting in agricultural areas, and some factors affect food security, namely economic factors or individual income. The presence of household food security affects the incidence of stunting. Stunting increases when there is no food security, which coincides with the pre-harvest season. Low food security (food variety and quantity) can negatively impact the risk of stunting. As health workers, nurses must undoubtedly play a role in reducing stunting rates, one of which is by providing education or becoming educators for the community about the importance of food security in reducing the incidence of stunting.